THE LEXICAL AND SEMANTIC FEATURES OF THE CONCEPT OF LABOR (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article explores the lexical, semantic, and cultural characteristics of the concept of labor in English and Uzbek languages. By examining dictionary definitions, metaphorical expressions, and culturally embedded idioms, the study highlights the complexity and richness of the concept. Comparative insights reveal both universal and culturally specific features associated with labor, reflecting societal values and worldviews encoded in language.